Determinant Factors of Gapoktan in Promoting Business Ventures: a Case Study of Sepakat Farmer Group in Nagari Canduang, West Sumatra - Wahyuni , Sri; Syahni, Rahmat; Fairuzi, Syofyan; Mahfuzh, Fuad (Jurnal AGRISEP, 2026)
Gapoktan (gabungan kelompok tani/farmer group associations) play a vital role in increasing the economic scale and operational efficiency of agricultural collectives, yet many face challenges in sustaining business ventures. The study therefore seeks to explore success factors for Gapoktan to sustain itself in commerce-related activities. The specific goals of this study are to discuss the role of Gapoktan, their partners, their collaborative partners, and factors that act as enablers for them. A qualitative descriptive method was employed, using Focus Group Discussions (FGD) with the Gapoktan chairperson, farmer group leaders, and the Agricultural Extension Center coordinator. According to the findings, the Sepakat Gapoktan is primarily engaged in three activities: (1) organic vegetable marketing; (2) compost production, and; (3) Biological Agent Service Information Center. The main factors contributing to the success of Gapoktan in its business ventures are: (1) effective leadership by the Gapoktan chairperson, (2) treating the association as a business entity rather than a social group, (3) engagement of local leaders, (4) commitment to terms of time, energy, and financial resources, 5) collaboration with external institutions.